Characteristic rotational behaviors of rod-shaped cargo revealed by automated five-dimensional single particle tracking. Issue 1 (December 2017) - Chen, Kuangcai; Gu, Yan; Sun, Wei; Dong,; Wang, Gufeng; Fan, Xinxin; Xia, Tian; Fang, Ning
Abstract We report an automated single particle tracking technique for tracking thex, y, z coordinates, azimuthal and elevation angles of anisotropic plasmonic gold nanorod probes in live cells. These five spatial coordinates are collectively referred to as 5D. This method overcomes a long-standing challenge in distinguishing rotational motions from translational motions in thez -axis in differential interference contrast microscopy to result in full disclosure of nanoscale motions with high accuracy. Transferrin-coated endocytic gold nanorod cargoes initially undergo active rotational diffusion and display characteristic rotational motions on the membrane. Then as the cargoes being enclosed in clathrin-coated pits, they slow down the active rotation and experience a quiet period before they restore active rotational diffusion after fission and eventually being transported away from the original entry spots. Finally, the 3D trajectories and the accompanying rotational motions of the cargoes are resolved accurately to render the intracellular transport process in live cells. Distinguishing rotational motions from translational motions in thez -axis has been a long-standing challenge. Here the authors develop a five-dimensional single particle tracking method to detect rotational behaviors of nanocargos during clathrin-mediated endocytosis and intracellular transport.